2016
DOI: 10.1089/acm.2015.0314
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation-Based Intervention Is Feasible, Acceptable, and Safe for Chronic Low Back Pain Requiring Long-Term Daily Opioid Therapy

Abstract: Objective: Although mindfulness meditation (MM) is increasingly used for chronic pain treatment, limited evidence supports its clinical application for opioid-treated chronic low back pain (CLBP). The goal of this study was to determine feasibility, acceptability, and safety of an MM-based intervention in patients with CLBP requiring daily opioid therapy. Design: 26-week pilot randomized controlled trial comparing MM-based intervention, combined with usual care, to usual care alone. Setting: Outpatient. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 43 publications
2
44
0
1
Order By: Relevance
“…In addition, the MM group received the MM intervention (eight weekly 2-hour group sessions, led by two trained and experienced therapists, and at-home MM practice at least 6 days/week during the whole study), described elsewhere. 15,16 The MM intervention was patterned after established curricula 23–25 and tailored to meet the psychophysical needs of patients with opioid-treated CLBP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the MM group received the MM intervention (eight weekly 2-hour group sessions, led by two trained and experienced therapists, and at-home MM practice at least 6 days/week during the whole study), described elsewhere. 15,16 The MM intervention was patterned after established curricula 23–25 and tailored to meet the psychophysical needs of patients with opioid-treated CLBP.…”
Section: Methodsmentioning
confidence: 99%
“…1116 Our 26-week pilot randomized-controlled trial (RCT, N=35) showed that MM was associated with reduced pain severity (p<0.05) and decreased sensitivity to heat-pain stimuli (p<0.05) among adults with disabling CLBP treated, on average, with a high-dose opioid therapy. 15 In addition, the MM intervention was found to be safe, feasible, and highly acceptable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Результаты клинических исследований демонстрируют, что добавление майндфулнесс к стандартной терапии хронической неспецифической БНЧС повышает эффективность лечения [44,45]. Применение майндфулнесс эффективно для уменьшения интенсивности боли у пациентов, принимающих слабые опиодные препараты [46,47], а также у пациентов старшей возрастной группы [48,49].…”
Section: групповые сессии когнитивно-поведенческой терапииunclassified
“…Several systematic reviews examining meditation interventions specifically in the chronic pain population have reported small but consistent improvements in pain, function and depression [18][19][20][21]. Meditation is commonly sought out by diverse people living with depression and chronic pain and the intervention is well received in these populations [22][23][24]. Sahaj Samadhi Meditation (SSM), a type of automatic self-transcending meditation, is easy to learn and master [25] and its processes can lead to stress reduction and deep relaxation [26].…”
Section: Introductionmentioning
confidence: 99%